Emodin Attenuates Pathological Cardiac Hypertrophy by Regulating Gene Expression Through Acetyl-histone-mediated Actions (P06-036-19). (13th June 2019) - Evans, Levi; Ferguson, Bradley
Abstract: Objectives: Epigenetic modifications regulate gene expression without changing DNA sequence and are reversible, highlighting their therapeutic potential for heart failure. Recent evidence suggests that food compounds can reverse these stress-induced epigenetic modifications, yet few studies have characterized their role as epigenetic regulators of heart health. Our objective tested the hypothesis that Emodin, an Antraquinone found in rhubarb, blocked pathological cardiac hypertrophy via acetyl-histone-mediated gene expression changes. Methods: To test this hypothesis, neonatal rat ventricular myocytes (NRVMs) were stimulated with phenylephrine (PE, 10 μM) to induce receptor-mediated pathological cardiac hypertrophy in the absence or presence of vehicle control or Emodin (10 μM) for 48 hours. Cells were subsequently 1) fixed for immunostaining and cell size quantification, 2) lysed for protein to assess HDAC activity and histone acetylation or 3) lysed for RNA to analyze transcriptome–wide changes in gene expression. A minimum of three experiments with an n = 3/group was performed and data quantified. One-way ANOVA with Tukey's post-hoc was performed unless otherwise specified. p < 0.05 was considered significant. Results: Emodin significantly blocked PE-induced hypertrophy. Emodin significantly inhibited HDAC activity concomitant to increased histone acetylation. Lastly, Emodin reversed stress-induced changes in gene expression. Conclusions: Our data suggest that Emodin inhibited pathological cardiac hypertrophy via acetyl-histone dependent regulation of gene expression. While animal studies are currently underway to examine the epigenetic actions for emodin in cardiac protection, our results support the role for food compounds like Emodin as epigenetic regulators of heart health. Funding Sources: This work is supported by the USDA NIFA (Hatch-NEV00727), the Dennis Meiss & Janet Ralston Fund for Nutri-epigenetic Research and by the National Institute for General Medical Sciences (NIGMS) of the NIH (P20 GM130459) to B.S.F. Core facilities used for Research were supported by NIGMS of the NIH (P20 GM103554).